Establishment and Clinical Application of a Method for Detecting T Lymphocyte Subsets by Cellular Immunochip Technology - Chen C; Liu YM; Xuan SX; Zhou MF; Zhou P; Cheng B; Lin JD; Yin WG; Li LH (Dove Medical Press, 2021)
Chen Chen,* Yan-Mei Liu,* Shu-Xia Xuan, Mei-Fang Zhou, Peng Zhou, Bin Cheng, Jin-Duan Lin, Wei-Guo Yin, Lin-Hai Li Department of Laboratory Medicine, The Sixth Affiliated Hospital of Guangzhou Medical University, Qingyuan People's Hospital, Qingyuan, People's Republic of China*These authors contributed equally to this workCorrespondence: Wei-Guo Yin; Lin-Hai LiDepartment of Laboratory Medicine, The Sixth Affiliated Hospital of Guangzhou Medical University, Qingyuan People's Hospital, Qingyuan, 511518, People's Republic of ChinaTel +86 763 311 3890Email wgy09dr_mn@163.com; lilinhai_abc@outlook.comObjective: To establish and verify the method for detecting the immune phenotype of peripheral blood T lymphocytes by cellular immune chip technology, analyze the immune status, and discuss its clinical diagnostic value of different populations in the Qingyuan area.Methods: First, a cellular immune chip was used to detect the number of T lymphocyte subsets CD3+, CD4+, CD8+, and CD4/CD8, followed by evaluating the accuracy and precision through a comparison with flow cytometry. After passing the performance verification, a large-scale detection was performed by a cellular immune chip in 8389 cases. Immunochip technology detects the expression of T lymphocyte subsets and analyzes the differences in cellular immune function among people with physical examination, inflammation, and cancer, as well as different cancer types and in genders.Results: The cell immunochip method and flow cytometry method have the same accuracy and precision in detecting specimens, and the former is fast and simple, and is suitable for clinical use; big data analysis is expected to establish a reference range for CD3+, CD4+, and CD8+ T cell counts in Qingyuan. There are statistical differences in CD3+, CD4+, CD8+ T cell counts in physical examination, inflammation and cancer populations; there are also certain differences in CD3+, CD4+, CD8+ T cell counts and CD4/CD8 ratios between different cancer types and different diseases.Conclusion: The method of cell immunochip technology to detect T lymphocyte subsets is simple and practical, with accurate results and rapid detection. It can be used for immune function monitoring and treatment prognosis evaluation of people with different diseases, and it is worthy of popularization and application in clinical practice.Keywords: T lymphocyte, physical examination, CD4/CD8, cellular immune chip